Cripple Creek, 1896. - Western Lithograph Co.; Phillips & Desjardins. (1896)
Bird's-eye-view.; AACR2: 651/1; 651/2; LC Panoramic maps (2nd ed.), 60; Perspective map not drawn to scale.; Includes text, illus., list "Some of the principal mines in the Cripple Creek Mining District," and inset "Victor."; Available also through the Library of Congress Web site as a raster image.